(untitled) (EAAE Joint Publishings, 2026)
he Stockholm Resilience Center has been developing data to help outline a safe space for human activities for a decade. This includes the activity of producing building materials, constructing and operating buildings, which is one of the most significant contributors to greenhouse gas emissions. The impact categories assessed by the worldwide scientific community at the Stockholm Resilience Center match the categories in the ISO standard LCA. This effort is also an expression of the Paris Agreement, which outlines the CO2 reduction each nation must achieve by 2030 to keep the temperature rise on the planet below 2.0- or 1.5 degrees C (UNFCCC 2016). Based on this, a team of universities and industry partners examined what it would take for the Danish construction sector to comply. One of the universities in the project described above took the initiative to develop an interdisciplinary course to investigate the necessary set-up to teach how to design buildings whose environmental impact is within planetary boundaries. The article describes the development process and the results of the first test run of the course in the summer of 2023. The course content is explained based on the discussions between the three educational institutions involved in the development and the pre- and post-evaluation of the 26 participating students, as well as semi-structured interviews with the students. The challenge in course development was whether it was even possible to design for and build within the planetary boundary and how to address this open question in a course design. The ideas and reasoning behind these course design decisions, as well as the results from the pilot course, are presented and discussed in the article.